The dynamics of coalition formation - a multilateral bargaining experiment with free timing of moves - James Tremewan; Christoph Vanberg (University of Heidelberg, Department of Economics, 2015)
We experimentally study behavior in a finitely repeated coalition formation game played in real time. Subjects interact in groups of three, bargaining over the distribution of payments which occur at regular time intervals. During a given interval, payments occur if and only if a majority is in agreement about their allocation. Aside from these rules, we purposefully impose little structure on the bargaining process. We investigate the frequency and stability of different types of agreements, as well as transitions between them. The most frequent agreement is an equal split between two players, leaving the third with nothing. The most stable is the three-way equal split. Transitions between agreements are frequent and generally consistent with myopic payoff maximization. We find evidence that both fairness concerns and risk aversion may explain the prevalence of the three-way equal split, and that loyalty can play a role in cementing coalitions.
urn:nbn:de:bsz:16-heidok-181595
Keywords: 330; Bargaining; group choice; experiments; coalition formation; Verhandlungstheorie; Dynamisches Spiel; Gruppenentscheidung; Theorie